Remarks on Addressing Food Loss and Waste - Malpass, David (World Bank, Washington, DC, 2020)
World Bank Group President David Malpass spoke about the pandemic that is having severe economic and health impacts around the world, and how the food sector is critical. He mentioned that the Coronavirus (COVID-19) has exposed long-standing problems in the global food system. He highlighted on the importance of reducing food loss and waste, which can increase food and nutrition security, reduce the environmental footprint of food systems, and improve the welfare of producers and consumers. He launched the new World Bank analysis that will help identify the right entry-points for countries to achieve their goals. He said that the new country diagnostics will help countries better target food loss and waste investments. He concluded by hoping that these reports motivate partners to find ways to cut food loss and waste, so that we end hunger and work together to create a healthy planet, healthy people and healthy economies.